A Comparative study on Prevalence of Diastasis Recti in Primipara and Multipara Undergone Full Term Normal Delivery - A Research Protocol - Simran Jaiswal1 , Shalaka Dhankar1 (Indian Journal of Forensic Medicine & Toxicology, 2021)
Background: Diastasis Recti is very common in women after pregnancy. Diastasis recti among womenshould be treated as soon as possible as it may cause various musculoskeletal dysfunctions. A digital caliperis a tool for assessing diastasis recti in postpartum women. It is a simple, fast, and reliable assessment toolfor assessing diastasis recti. Objective: The objective of the study is to find the prevalence of Diastasis Rectiin Primipara and Multipara undergone full-term normal delivery and to compare the prevalence of diastasisrecti in the both of the groups Method: This study will be carried out in Physiotherapy OPD, Ravi NairPhysiotherapy College and AVBRH, Sawangi (Meghe), Wardha. Diastasis recti will be evaluated in fullterm normal delivery females. Diastasis recti will be compared in primipara and multipara using a digitalcaliper. Results: The result of the study will be estimated by the statistical analysis of the data and will bediscussed after the study is completed.Conclusion: After going through various studies, many studies haveindicated that the prevalence of diastasis recti abdominis is commonly seen in multipara undergone cesareansection delivery. Very few studies indicate the prevalence of diastasis recti abdominis in primipara and alsowomen underwent full-term normal delivery. Therefore, the current study is carried outreach a conclusion tofind whether there is any discrepancy of the prevalence of diastasis recti abdominis between primipara andmultipara in females undergone full-term normal delivery.